Elastic Organic Crystals as Bioinspired Hair‐Like Sensors - Yousuf, Soha; Mahmoud Halabi, Jad; Tahir, Ibrahim; Ahmed, Ejaz; Rezgui, Rachid; Li, Liang; Laws, Praveen; Daqaq, Mohammed; Naumov, Panče (Angewandte Chemie, 2023)
One of the typical haptic elements are natural hairy structures that animals and plants rely on for feedback. Although these hair sensors are an admirable inspiration, the development of active flow sensing components having low elastic moduli and high aspect ratios remains a challenge. Here, we report a new sensing approach based on a flexible, thin and optically transmissive organic crystal of high aspect ratio, which is stamped with fluorescent dye for tracking. When subjected to gas flow and exposed to laser, the crystal bends due to exerted pressure and acts as an optical flow (hair) sensor with low detection limit (≈1.578 m s−1) and fast response time (≈2.70 s). The air‐flow‐induced crystal deformation and flow dynamics response are modelled by finite element analysis. Due to having a simple design and being lightweight and mechanically robust this prototypical crystal hair‐like sensor opens prospects for a new class of sensing devices ranging from wearable electronics to aeronautics. A high‐aspect ratio, elastically bendable organic single crystal is presented as a hair air‐flow sensor. The crystal acts as a passive light‐transducing medium that is stamped with a fluorescent dye to track its deformation upon exposure to nitrogen gas. Furthermore, the modelling analysis of the air‐flow‐induced crystal deformation, and the response to flow dynamics around the crystal body are presented.